Triumphant Technology and Minimal Man: The Technological Society, Science Fiction Films, and Ridley Scott's Alien. - Matheson, T.J. (Extrapolation (Kent State University Press))
Discusses Ridley Scott's 1979 film `Alien.' Examinations of `Alien' in scholarly journals; J.P. Telotte; Jacques Ellul's `The Technological Society'; Technique; `Nostromo'; More.